2020
DOI: 10.1111/odi.13691
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of pretreatment cardiovascular biomarkers in head and neck squamous cell carcinoma

Abstract: Objectives To examine the prognostic significance of pretreatment C‐reactive protein (CRP), N‐terminal pro‐brain natriuretic peptide (NT‐proBNP), and cardiac troponin T (cTnT) levels on all‐cause mortality 3 years after head and neck squamous cell carcinoma (HNSCC) diagnosis. Subjects and Methods Data from 118 consecutive HNSCC patients, treated between 2012 and 2015, were evaluated prospectively. The impact of CRP, high‐sensitive (hs)‐cTnT, and NT‐proBNP levels on the 3‐year overall survival was estimated usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Previous study has shown that pretreatment hs-cTnT had no influence over the prognosis in patients with head and neck squamous cell carcinoma [ 10 ]. These finding suggest that troponin may have different prognostic value in different cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study has shown that pretreatment hs-cTnT had no influence over the prognosis in patients with head and neck squamous cell carcinoma [ 10 ]. These finding suggest that troponin may have different prognostic value in different cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing interest in the relationship between cancer therapy and cardiovascular complications such as pericardial and myocardial disease, left ventricular dysfunction, and ultimately heart failure [ 7 ]. However, there are only a few studies dedicated to investigating the association between cardiac biomarkers with all-cause death in cancer patients prior to the tumor resection surgery [ 8 10 ]. Such studies had small sample sizes, etiological heterogeneity and different conclusions [ 11 ], therefore, no consensus can be reached.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the inflammatory link between tumors, their microenvironment, and the systemic response [7], different inflammatory markers were analyzed for their prognostic potential in various cancer entities including head and neck malignancies. Studies have shown the correlation of survival outcome in patients with head and neck carcinoma with several different inflammation-associated markers such as the neutrophil-to-lymphocyte ratio (NLR) [8,9], platelet-to-lymphocyte ratio (PLR) [10], and C-reactive protein (CRP) [11]. In our previous study, we assessed the prognostic significance of certain inflammatory biomarkers in ACC and observed an association of outcome with NLR values [12].…”
Section: Introductionmentioning
confidence: 99%